Pembentukan Galur Mandul Jantan Baru Padi Hibrida Tahan Penyakit Hawar Daun Bakteri dan Hama Wereng Batang Coklat - Nugraha, Yudhistira; Munarso, Yuniati P.; Satoto, Satoto (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
The presently available cytoplasmic male sterile lines (CMS) commonly used to develop rice hybrids in Indonesia are susceptible to major pests and diseases. Research was conducted to develop new cytoplasmic male sterile lines which are highly resistant to major pests and diseases. Two new cytoplasmic male sterile rice lines, GMJ4A and GMJ5A, were developed using backcross method, derived from crosses of BP455G-PN-13-2-1-1-10-MR-3-1 and B11005E-MR-4-2-1, which were identified as completely sterile on a test cross nursery. The following season, sterile F1 generations were successively backcrossed until stable sterile plants were obtained in 2006. Seeds of the two cytoplasmic sterile lines were mass produced at Muara, Bogor, in 2006. GMJ4A and GMJ5A are resistant to bacterial leaf blight patotipe IV and VIII. Both lines are resistant to brown plant hopper in the green house test with scores of 1 to 3. The hybrid combinations involving GMJ4A and GMJ5A were evaluated in an observational yield test at Muara during dry season of 2007 and at Kuningan in dry season 2009. The level of grain yield heterosis were better than the check varieties. These two lines are expected to be used as a replacement for the existing CMS lines.